Study of changes in the process of blood coagulation in chronic pancreatitis in rats (Experimental biology, 2015)
In this laboratory work at a pancreatitis the process of hemopexis is activated, it is a basic criterion of sharp pancreatitis.
Keywords: pancreatit; сoagulation; lymph; pancreatic; fibrinolysis; ligature